Olfactory instruction for fear: neural system analysis - Canteras, Newton S.; Pavesi, Eloisa; Carobrez, Antonio P. (Frontiers in Neuroscience, 2015)
Studies using cat odor have led to detailed mapping of neural sites engaged in innate and contextual fear responses. Here, we reviewed three lines of work examining the dynamics of the neural systems that organize innate and learned fear responses to cat odor. In the first, we explored the neural systems involved in innate fear responses and in the different stages of fear conditioning to cat odor (i.e., acquisition and expression), with a particular emphasis on the role of the dorsal premammillary nucleus (PMd) and the dorsolateral periaqueductal gray (PAGdl) as key sites that influence innate and contextual conditioning. In the second line of studies, we reviewed how chemical stimulation of these sites (i.e., the PMd and PAGdl) may serve as a useful unconditioned stimulus in an olfactory fear conditioning paradigm; these experiments provide an interesting perspective for the understanding of learned fear to predator odor. Finally, in the third line of studies, we explored the fact that neutral odors that acquire an aversive valence in a shock-paired conditioning paradigm may mimic predator odor and mobilize elements of the hypothalamic predator-responsive circuit.